2019
DOI: 10.1016/j.bbmt.2018.12.766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP3A4, CYP3A5, and ABCB1 Polymorphisms on Intravenous Tacrolimus Exposure and Adverse Events in Adult Allogeneic Stem Cell Transplant Patients

Abstract: A B S T R A C T Pharmacogenetics influences oral tacrolimus exposure; however, little data exist regarding i.v. tacrolimus. We investigated the impact of genetic polymorphisms in CYP3A4, CYP3A5, and ABCB1 on i.v. tacrolimus exposure and toxicity in adult patients receiving an allogeneic hematopoietic stem cell transplant for hematologic malignancies. Germline DNA was extracted from buccal swabs and genotyped for CYP3A4, CYP3A5, and ABCB1 polymorphisms. Continuous i.v. infusion of tacrolimus .03 mg/kg/day was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
19
2
Order By: Relevance
“…Achieving the tacrolimus target trough is important to reduce nephrotoxicity resulting from supratherapeutic tacrolimus concentrations. Three loss-of-function germline variants located in the exonic regions of ABCB1 (rs1128503, C1236T; rs2032582, C2677T; rs1045642, C3435T) have been implicated in both inter-patient tacrolimus PK variability and treatment-emergent toxicities [30][31][32]. In our study, AKI was not significantly associated with any of the ABCB1 or CYP3A4/5 SNPs.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Achieving the tacrolimus target trough is important to reduce nephrotoxicity resulting from supratherapeutic tacrolimus concentrations. Three loss-of-function germline variants located in the exonic regions of ABCB1 (rs1128503, C1236T; rs2032582, C2677T; rs1045642, C3435T) have been implicated in both inter-patient tacrolimus PK variability and treatment-emergent toxicities [30][31][32]. In our study, AKI was not significantly associated with any of the ABCB1 or CYP3A4/5 SNPs.…”
Section: Discussioncontrasting
confidence: 45%
“…ABCB1 encodes P-gp, and it is highly expressed in both the enterocytes and hepatocytes, and thus ABCB1 SNPs could explain interindividual tacrolimus absorption and exposure [29]. However, P-gp is also located on the apical membrane of renal tubular epithelial cells, and SNPs have been associated with increased risk of tacrolimus-induced nephrotoxicity [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germline genetic variations in genes that encode for proteins central to tacrolimus metabolism and transport are associated with interindividual tacrolimus in PK/PD variability in both the solid organ and the HCT patient populations 9–11 . CYP3A5 has been identified as a gene with functional variants known to alter tacrolimus PK in seminal guidelines from the Clinical Pharmacogenetics Implementation Consortium and the Dutch Pharmacogenetics Working Group 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a curative therapy for several hematological malignancies and nonmalignant diseases, because of its substantial morbidity and mortality, posttransplant survival, relapse and the occurrence of GVHD are issues concerned by both clinicians and researchers. Although varieties of studies [1][2][3][4] have reported the potential relationship of single nucleotide polymorphisms (SNPs) in genes encoding minor histocompatibility antigens, cytokine, chemokines and even drug-metabolizing enzymes with transplant outcomes, there are currently no well-established predicted biomarkers of clinical results after allo-HSCT. Therefore, investigations aiming to explore the pretransplantation predictors of genetic variants to assist in the risk assessment of adverse outcomes is critical, which can provide potential targets for novel prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%